Unsur Intrinsik dan Kondisi Sosial Cerpen Mamadu Karya Ketut Sariani: Analisis Unsur Intrinsik dan Kondisi Sosial Dalam Cerpen Mamadu Karya Ketut Sariani - Sariani, Ni Ketut Astri; Cahyani, Ni Made Cintya; Apriliana, Ni Kadek; Widayanti, Ni Putu Eka; Paramitha, Ni Made Ayu Susanthi Pradnya (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2024)
Literature is very closely related to society. As time goes by, many literary works also experience developments that people are not aware of, giving rise to modern Balinese literary works. One of the modern Balinese literary works is the short story. Short story is a type of prose where the content of the story is not a real event and is just made up. Short story tends to be short, concise, and straight to the point when compared to other longer works of fiction such as novels. In this modern Balinese literary work, it can be used as a medium to channel the aspirations of Balinese krama, as is the case in the short story literary work entitled “Mamadu” by Ketut Sariani. In this research, the researcher will discuss the analysis of intrinsic elements and social conditions in the short story Mamadu by Ketut Sariani